STIMULASI TITIK REPRODUKSI DENGAN LASERPUNKTUR SEMIKONDUKTOR TERHADAP PENAMPILAN BIRAHI SAPI BALI (Bos sondaicus) - Nisa, Hanifah Khairun; Budiarto, Budiarto; Adikara, Tatang Santanu; Hermadi, Herry Agoes; Soeharsono, Soeharsono; Mustofa, Imam (Journal of Basic Medical Veterinary, 2020)
This research to know the stimulation of reproduction point with a semiconductor laserpuncture to estrous synchronization of Bali Cattle was conducted in Loka Penelitian Sapi Potong Grati-Pasuruan, East Java. Estrous synchronization is a technique to get the sign of estrous and ovulation (estrous outside of estrous cycle) to be easier to detect estrous, synchronization of breeding, and shorter of calving interval. Laserpuncture was applied on 8 head bali cattles at 14 reproduction acupuncture points, 10 second for each point, 3 times frequency with interval 1 day (20-24 times). The variabel of this assessment were respons and signs of estrous, synchronized of estrous with Chi square test and T-test method. Result showed that there was significant correlation between semiconductor laserpuncture with estrous synchronization (p < 0,05). The result of assessment 8 (100%) head bali cattle was estrous. The respons of estrous appeared 1 head (12,5%) on 5th day (4th day post laserpuncture), 4 head (50%) on 6th day (5th day post laserpuncture) 1 head (12,5) on 8th day (7th day post laserpuncture), and 2 head (25%) on 10th day (9th day post laserpuncture). This result showed that semi conductor laserpuncture technology was effective to stimulate estrous synchronization and resulting ovulation, with the evidence that conception was occurred.